Carbon fibre reinforced polymer in strengthening and enhancing reinforced concrete beams / [electronic resource] - Thirunavakarasu Venugopal, 1982- , author (2015)
Project Paper (Sarjana Muda Kejuruteraan (Awam - Struktur)) - Universiti Teknologi Malaysia, 2015